Hiding, sheltering, and borrowing identities : avenues of rescue during the Holocaust - Mikhman, Dan (2017)
"This present volume, which includes a selection of the papers presented at the 18th Yad Vashem bi-annual international scholars' conference dedicated to the topic 'Hiding, Sheltering, and Borrowing Identities: Avenues of Rescue During the Holocaust' (December 19-21, 2010), is an attempt to add new insights to the multi-faceted picture of rescue at the grassroots level."